Effect factors analysis and characteristic of freeze-thaw deformation of fracture rock - Shenghua Cui; Qingwen Yang; Xuelian Rui; Yuyang Zhang (地质科技通报, 2021)
In the cold and high-altitude regions of Sichuan Provence, the rock failure caused by freeze-thaw deformation has a significant impact on projects. In order to study the cyclic freeze-thaw characteristics of rock mass under different fracture conditions, the phyllite and sandstone were taken from this area. The rock samples with different joint lengths, opening, number of joints were conducted with 50 cycles of freeze-thaw tests under ±20℃. The test results showed that the saturated rock had process of freeze contract→freeze expand→freeze contract→thaw expand→thaw contract→thaw expand. The dry rock had process of freeze contract→melt expansion. The relationship between freeze-thaw cycle times and εd was studied. The length of joint, opening and number of joints had an influence on freeze-thaw deformation of dry sample. Select the residual deformation εr as an index to study the increasing of εr with increasing of εd for phyllite and sandstone samples under the water saturation conditions. The relationship between εr and εd had been obtained. The decreasing of uniaxial compressive strength of dry and saturated samples with increasing of the number of freeze-thaw cycles was analyzed. The linear relationship between freeze-thaw times and sample deterioration was determined. Finally, the influence mechanisms of water saturation condition, lithology and fracture condition on freeze-thaw cyclic deformation of rock mass were discussed.